Pengaruh Pembelajaran Pendidikan Agama Islam Berbasis Aplikasi Digital Wordwall terhadap Pendidikan Karakter Peserta didik Madrasah Aliyah - Maulida, Siti; Pratomo, Herdianto Wahyu; Nurhidayat, Nurhidayat (Universitas Negeri Padang, 2025)
This study aims to assess the effect of using digital Wordwall applications in Islamic Religious Education Learning (PAI) to strengthen students' character education in MAN 2 Majalengka. The background of this study departs from the importance of innovation in Islamic Religious Education Learning to strengthen the character of learners effectively and contextually. This study uses a quantitative approach with a quasi-experimental design in the form of a pre-test-post-test control group. The sample consisted of 70 students of Class XI who were divided into two groups: the experimental group (n=36) who participated in Wordwall-based Islamic Religious Education Learning , and the control group (n=34) who received conventional Islamic Religious Education Learning. Data collection was conducted through questionnaires that measured the five main indicators of strengthening Character Education (PPK), namely religious, nationalist, Independent, mutual aid, and integrity. Questionnaires were administered before and after treatment in both groups. The results of the data analysis showed that there was an increase in character in both groups, but the increase in the experimental group was statistically more significant than the control group (p<0.05). These findings indicate that using the Wordwall application can positively contribute to the formation and strengthening of the character of learners. Therefore, the application of interactive digital learning media such as Wordwall is highly recommended to be integrated into Islamic Religious Education Learning in madrasah as an effort to build character education that is more effective and fun.